PERANCANGAN INSTALASI PENGOLAH AIR LIMBAH DOMESTIK TERPADU PADA KAWASAN KAMPUNG NELAYAN DI KOTA BENGKULU - Meilani Belladona; Hernowo Novi Yanto (Universitas Bengkulu, 2019)
Pasar Bengkulu region has the level of high population and located along the coast of zakat so that the majority of livelihood population in this area were fishermen. Sanitation in these coastal regions are less good, this looks a litter of garbages on the yard, drainage channel does not flows, and some homes that dispose is to the yard. This research aims to make the draft design integrated wastewater treatment. The method used to spread the questionnaire. A simple statistical analysis is used to make social analysis of the public about the level of education that affect the level of knowledge of citizens about sanitation. Social analysis results showed that the level of education affect lack of knowledge residents about wastewater and sanitation. Based on discharge waste obtained design of wastewater treatment integrated consisting of dividing tub fats and oils as to dimensions 3mx4mx2m, equalization tub 4 m x 4.8 m x 2 m, anaerobic contactor tub 8.5mx4mx2m, aerobic contactor tub 2.5 x 2 m x 2 m and media bed 2.9mx4mx2m, disposition of late 3mx4mx2m with a thick wall of 20 cm and concrete quality K275. This portion of processed water or everything can be thrown into a body of water. Based on the results of the analysis needs a socialization in importance of sanitation